An approach for identifying design principles in argument systems : A preliminary report - Capobianco, Marcela (2006)
Artificial Intelligence deals with the challenge of modeling commonsense reasoning. In the last fifteen years argument-based systems have came forward to meet this challenge as knowledge representation and reasoning tools able to model incomplete and conflicting information. We believe that the argumentation field has sufficiently matured in the last years to deserve a formal analysis of properties of the main existing argumentation systems. In this work we propose a set of general principles for argumentation enunciated in abstract terms, that can be analyzed in the context of several argumention formalisms. We intend that these principles help to achieve a unified formal view of argumentation properties.